Building Mounds. Longhouses, Coastal Mounds and Cultural Connections: Norway and the Northern Isles, c ad 800-1200. (1st November 2013) - Harrison, Jane
Abstract : WHY WERE important Viking longhouses built on large mounds of sand and then repeatedly rebuilt in precisely the same apparently challenging location? Generations of Viking-late Norse people did so, on sandy bays along the coasts of the Northern Isles of the United Kingdom. These prominent, 'layered-up' longhouse complexes were landscape statements. They reflected, in their location and the detail of their construction and use, the social attitudes and arrangements of those who lived in and visited them. The settlements played a pivotal role in power relationships and in the organisation of the local economy. This article explores the meaning of these focal settlement mounds through landscape archaeology; investigates building practices, stratigraphic detail and place-name associations; looks at their cultural roots in Scandinavia; and considers the role they played in the development of local social and political structures in Orkney.